Policy makers' perspectives on tobacco control advocates' roles in regulation development - Montini, T. (BMJ Group, 2001)
OBJECTIVE—To identify, from policy makers' perspectives, strategies that enhance tobacco control advocates' effectiveness in the regulatory arena. DESIGN—Key informant interview component of a comparative case study of regulatory agencies in the USA. SUBJECTS—Policy makers involved in the development of four regulatory tobacco control policies (three state and one federal). METHODS—Interviews of policy makers, field notes, and deliberation minutes were coded inductively. RESULTS—Policy makers considered both written commentary and public testimony when developing tobacco control regulations. They triaged written commentary based upon whether the document was from a peer reviewed journal, a summary of research evidence, or from a source considered credible. They coped with in-person testimony by avoiding being diverted from the scientific evidence, and by assessing the presenters' credibility. Policy makers suggested that tobacco control advocates should: present science in a format that is well organised and easily absorbed; engage scientific experts to participate in the regulatory process; and lobby to support the tobacco control efforts of the regulatory agency. CONCLUSIONS—There is an important role for tobacco control advocates in the policy development process in regulatory agencies.   Keywords: health policy; regulations; policy makers